Effects of different drying methods on the total phenolics, flavonoids and tannins of tsaang-gubat (Carmona retusa (vahl) Masam.] - Maza, Maria Isabel Beatrice R.
ABSTRACT The research aims to determine the effects of different drying methods - air-drying, cabinet drying, freeze-drying, to the total phenolic content (TPC), total flavonoid content (TFC), condensed tannin content (CTC), and % Inhibition (H) of Tsaang-gubat tea infused at boiling and room temperatures through classic spectrophotometric methods of phenolic compound quantification. The general trend of the values according to effects of drying was: air-dried > cabinet-dried > freeze-dried > fresh (control). Total phenolic content determined from dried samples (infused in boiling temperature) are: air-drying = 27.05 mg GAE/g sample, cabinet-drying = 18.89 mg CE/g sample, freeze-drying = 12.32 mg CE/g sample. Results showed substantial amounts of total phenolics but lower fractions of total flavonoids and condensed tannins. CTC have higher values than TFC. The tea infused at 100°C yielded the following range of values for every phenolic test: TPC = 5.01-27.05 mg GAE/g sample; TFC = 0.2-0.45 mg CE/g sample; CTC = 0.42-1.18 mg CE/g sample. Meanwhile, results from room temperature infusion are as follows: TPC = 2.08-18.61 mg GAE/g sample; TFC = 0.13-0.27 mg GAE/g sample; CTC = 0.30-1.09 mg GAE/g sample. The highest values for all phenolic tests, in two infusion temperatures are from air-dried samples and the lowest values were those from the fresh samples as the control. From the results, it was deduced that drying methods positively affect the phenolics of Tsaang-gubat because of the higher values relative to the control. It was also verified that infusions at higher temperature (100°C) is a better method compared to room temperature infusion.